Collateral As Expired Solution a Risk of Mudharabah Financing (Case Study of Bank Syariah Mandiri Bank KCP. Ponorogo) - Retnowati, May Shinta (AL-IKTISAB: Journal of Islamic Economic Law, 2018)
The practice of bank or non-bank financial institutions, seen from its development, is constantly changing. Since the growth of the Islamic economic system that emerged since 1992, using the usury-free system or profit sharing operated by Islamic banks, was developed to create even economic stability among the people. Sharia bank operational systems include funding, lending (financing), and services using muamalah contracts. The financing system for sharia banking products uses mudharabah contracts, but the implementation of collateral is one of the mudharabah financing solutions This research was conducted to determine mudharabah financing practices in BSM KCP. Ponorogo, how to settle defaults and balance collateral and profit sharing, using a qualitative research method that is descriptive and tends to use analysis. In the technique of collecting data with interviews, observation and documentation. In this study the implementation of contract in BSM, the customer does not know the intent by clearly the contents of the contract that has been signed and the customer does not get a copy of the contract documentation, so that it can lead to a risk of default later, in resolving disputes practiced at BSM to customers Paying is by continuous billing, restructuring, and strategy execution, while the more BSM is more often used by BSM is the execution of strategies in a family manner that can benefit both parties, but BSM leaves hands on the sale value of collateral carried out by the customer. On the balance of collateral risk and profit sharing that occurs in the practice of Islamic bank financing. Shows more collateral value than the value of financing received by the customer so that if there is a default financing or a customer fails to pay more to the bank, because the assets of the collateral are held by the bank, while for the results determined at the beginning of the contract consideration that the customer's business is in good condition because of obtaining additional funds from the bank, that this is the case of unclear division (gharar).